2018
DOI: 10.1016/j.cub.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Spindle Refractoriness Segregates Periods of Memory Reactivation

Abstract: The stability of long-term memories is enhanced by reactivation during sleep. Correlative evidence has linked memory reactivation with thalamocortical sleep spindles, although their functional role is not fully understood. Our initial study replicated this correlation and also demonstrated a novel rhythmicity to spindles, such that a spindle is more likely to occur approximately 3-6 s following a prior spindle. We leveraged this rhythmicity to test the role of spindles in memory by using real-time spindle trac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
257
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(284 citation statements)
references
References 56 publications
26
257
1
Order By: Relevance
“…We observed SS in HC with no ictal or interictal involvement, and HC-SS are observed in animals (Miyawaki and Diba, 2016), suggesting that they represent healthy activity. Our confirmation of phase-modulation of HC-ripples by HC-SS, and our demonstration of their coordination with NC-GE, provides a possible framework for HC-NC information transfer, as previously suggested (Siapas and Wilson, 1998;Sirota et al, 2003;Staresina et al, 2015) Antony et al, 2018). However, despite our efforts to eliminate contamination by epileptiform events, our study is limited by the possibility of pathological restructuring, and the possible role of SSR in memory replay is unconfirmed in mechanistic studies.…”
Section: Discussionsupporting
confidence: 70%
“…We observed SS in HC with no ictal or interictal involvement, and HC-SS are observed in animals (Miyawaki and Diba, 2016), suggesting that they represent healthy activity. Our confirmation of phase-modulation of HC-ripples by HC-SS, and our demonstration of their coordination with NC-GE, provides a possible framework for HC-NC information transfer, as previously suggested (Siapas and Wilson, 1998;Sirota et al, 2003;Staresina et al, 2015) Antony et al, 2018). However, despite our efforts to eliminate contamination by epileptiform events, our study is limited by the possibility of pathological restructuring, and the possible role of SSR in memory replay is unconfirmed in mechanistic studies.…”
Section: Discussionsupporting
confidence: 70%
“…Similar to previous findings, our TFR results have shown that up-phases of slow waves were associated with a robust increase of 44±26% in fast sigma power (p<0.001, d=0.77), with a center frequency of ~16 Hz and extending to higher frequencies (slow gamma, ~30 Hz). Interestingly, at the end of the 2-s analysis window, there was also a suppression of activity in the sigma band following the enhancement (p=0.03, d=-0.38; mean decrease -13±6%), which is in line with previous findings on refractory periods of spindle occurrence (Antony et al, 2018). Superimposed grand-averaged ERP waveforms (in C4 target channel) for STIM (solid line) and SHAM (dashed line) conditions in an overlay, with (left) time-frequency power plots (relative change in power between STIM and SHAM collapsed across all channels) and (right) time-frequency t-value plots (shaded area indicates nonsignificant difference between conditions, cluster corrected two-sided p<.05).…”
Section: A Erp and Power Analysissupporting
confidence: 91%
“…To deal with this possible bias, we conducted two complementary analyses ( Supplementary Figure 1). First, we regressed out pre-sleep results to eliminate set-dependent effects of regression to the mean 20,26 (see Methods). This analysis produced similar results, with a significant effect for cuing (F(1,30)=17.89, p<0.001) and a nonsignificant interaction between set-size and cuing status (F(2,30)=0.11, p=0.9).…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the experiment, we collected scalp electroencephalographic data. We used these data for sleep staging and also to analyze responses to cue presentation during sleep, focusing on two frequency bands shown to be modulated by cues in previous studies 26,31 . The sigma range (11)(12)(13)(14)(15)(16) Hz) encompasses sleep spindles, which are ramped waves lasting between 500-3000 ms. Spindles have been linked to memory consolidation (see 32 for review).…”
Section: Delta and Sigma Activity After Cue Presentation During Sleepmentioning
confidence: 99%